Perencanaan Komunikasi Pemerintah Daerah Buton Utara dalam Pembangunan - Syahruddin; Mardiana; Paramitha Purwita Sari (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2021)
In terms of infrastructure, North Buton District does not yet have adequate communication facilities. This is an obstacle in carrying out the development of North Buton, which incidentally is a means of supporting the development of North Buton Regency as a whole in the future. Therefore, effective communication is needed, namely by planning communication. How the local government can further analyze and study the objective conditions of the community. This research was conducted at the Regional Secretariat of North Buton Regency which is an institution that extends the hands of the Regional Government in the field of government administration and regional development, including aspects of the communication planning carried out. The technique of determining informants is by purposive sampling, namely the determination of informants intentionally. The selected informants were 6 informants. Efforts to obtain relevant data are carried out using in depth interviews for data collection with predetermined informants. The theory used in this research is the theory of communication planning. The results of this study are that communication planning in development by the North Buton Regional Secretariat is marked by the implementation of communication planning stages that support the smooth running of development through persuasive and informative messages.